Influence of Smallmouth Bass Predation on Recruitment of Age‐0 Yellow Perch in South Dakota Glacial Lakes. (13th July 2015) - Dembkowski, Daniel J.; Willis, D. W.; Blackwell, B. G.; Chipps, S. R.; Bacula, T. D.; Wuellner, M. R.
Abstract: We estimated the influence of predation by Smallmouth Bass Micropterus dolomieu on recruitment of age‐0 Yellow Perch Perca flavescens in two northeastern South Dakota glacial lakes. We estimated a likely range in consumption of age‐0 Yellow Perch using Smallmouth Bass diet information from two time periods when age‐0 Yellow Perch constituted high (2008) and low (2012 and 2013) proportions of Smallmouth Bass diets, and bass population size estimates as inputs in a bioenergetics model. The proportion of age‐0 Yellow Perch consumed by the Smallmouth Bass populations was determined by comparing estimates of consumption with estimates of age‐0 perch production. During 2008, age‐0 Yellow Perch constituted between 0% and 42% of Smallmouth Bass diets by weight, whereas during 2012 and 2013, age‐0 perch constituted between 0% and 20% of bass diets by weight. Across both lakes and time periods, production of age‐0 Yellow Perch ranged from 0.32 to 1.78 kg·ha −1 ·week −1 . Estimates of Smallmouth Bass consumption measured during the same intervals ranged from 0.06 to 0.33 kg·ha −1 ·week −1, equating to consumption of between 1% and 34% of the available Yellow Perch biomass. Given current conditions relative to Smallmouth Bass abundance and consumption dynamics and production of age‐0 Yellow Perch, it does not appear that Smallmouth Bass predation acts as a singular factor limiting recruitment of age‐0 Yellow Perch in our study lakes. However, future research and management initiatives should recognize that the long‐term impact of Smallmouth Bass predation is not static and will likely fluctuate depending on environmental (e.g., temperature) and biotic (e.g., trends in macrophyte abundance, predator and prey population structure and abundance, and predatory fish assemblage dynamics) characteristics. Received December 19, 2014; accepted April 20, 2015